Limits of Analogy in the Mechanism of Judicial Reduction of Property Sanctions - MIKRYUKOV, Viktor A. (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The relevance of this study is due to modern lawyers and law enforcement officials’ increased attention to the problems of using the analogy method in practical jurisprudence, the acute need to search for scientifically substantiated parameters of using this method in the mechanism of property sanctions judicial reduction. The role of the analogy method in the mechanism of judicial adjustment of property sanctions amount is clarified and legal limits of its application are established. The methods used: analysis, synthesis, abstraction, specification, comparative legal, formal legal and technical legal. The study shows the formation of a positive attitude of lawyers to the institution of judicial control over the property sanctions amount justification for civil violations and other compensatory payments to participants in the economic transactions. The findings can contribute to the doctrinal foundations strengthening for applying the analogy of law and the analogy of justice. Recommendations for the current legislation improving and application are formulated. For prevention of extrajudicial situational blocking of the formally lawful but undesirable economic behavior using of specially created legislative tools is proposed, and in their absence - resorting to the principle of inadmissibility of abusing the law.